Effect of seed size, treatment and sowing depth on quality and yield of Ethiopian wheat (Triticum Spp.), faba bean (Vicia faba L.) and chickpea (Cicer arietinum L.) cultivars - Mengistie, Demissie Mitiku (University of the Free State, 2000)
This study was undertaken in an attempt to obtain information on the quality of seed produced by some of the important crops grown in Ethiopia. Bread and durum wheat was chosen amongst cereals while chickpea and faba bean represented pulses. For all crops two cultivars were included except in the case of durum wheat where a third South African cultivar was additionally investigated. All experiments were carried out at the Small Grain Institute, Bethlehem, South Africa under laboratory and field conditions. The main objectives of this study were 1) to classify seeds of each crop into three different sizes (small, medium and large) and to characterize seeds in terms of kernel mass, hectolitre mass, moisture content and protein content where applicable, 2) to determine the differences in germination potential of untreated seeds and seeds treated with different fungicides under laboratory and field conditions, 3) to evaluate the field performances of different seedlots, including yield components, by means of agronomic parameters, 4) to investigate the effect of two different sowing depths on emergence, seed yield and other yield components and 5) to statistically determine cultivar, seed size, fungicide treatment and sowing depth interactions in a variety of ways. Of the two Ethiopian bread wheat cultivars, Mitikie outperformed Kubsa under laboratory and field conditions for most of the seed quality parameters evaluated. The main reason appeared to be the fact that deeper planted seeds performed well, probably due to longer coleoptile lengths of seedlings, which in turn was positively associated with strong and taller plants. When soil moisture is minimal, as is the case in semi-arid regions, it is possible to plant seeds of this variety deeper than normal in order to utilize soil moisture better. On average, small sized bread wheat seeds performed worst of all and large sized seeds best in terms of most of the measured parameters. Large seeds contributed to a 13.8% increase in seedling emergence and produced plants with a 22.1 % higher yield as well as 11.8% increase in above ground biomass. The effect of fungicides on the field performance of bread wheat seeds was less pronounced as compared to that of seed size. Seedling emergence from shallow planted (5 cm) bread wheat seeds was much better than from deep planted (9 cm) ones. However, although the seed protein content of seeds harvested from plants grown from deep plantedseeds were higher than that from shallow planted ones, shallow planting is still recommended for the Eastern Free State area on grounds of the overall performance of these seeds observed in this study. Durum wheat cultivars performed in a similar fashion as bread wheat. Seedlings of semi-dwarf durum wheat cultivars, as was the case for semi-dwarf bread wheat cultivars, showed longer root lengths than did the tall cultivars. Moreover, seeds from the semi-dwarf cultivar, Gerardo, produced taller plants than Orania and outyielded both other cultivars. Some weevil damage was observed in seeds of Kilinto and therefore its true performance could not be evaluated properly. Large sized durum wheat seeds outperformed the medium and small ones in most respects. Fungicide treatments also had an improving effect on seed performance compared to untreated control seeds. Seedling emergence was also greatly improved by shallow planting and this was reflected in significantly higher yields. The seed protein content, as was the case in bread wheat, were significantly higher in seeds harvested from plants grown from deep-planted seeds except in the case of Gerardo. Seed treatment with Vitavax Plus, together with deep planting, had the most significant increasing effect on the protein content in durum wheat seeds. In comparing the two faba bean cultivars, it was clear that Kuse outperformed Cs 20dk in terms of most of the evaluated parameters under both laboratory and field conditions. Similar to the previous two crops, large sized seeds appeared to outperform the other two seed size groups in most respects. However, surprisingly the small sized seeds produced seedlings with longer epicotyls but this had no real effect on the other quality parameters. Moreover, the fungicide Dividend also had some improving effect on the germination of faba bean seeds. Celest, however, significantly reduced the root length of seedlings compared to the other treatments, and also on grounds of the outcome observed by means of other parameters, Celest is not recommended for treatment of faba bean seeds. Deep planted (10-12 cm) faba bean seeds outperformed the shallow planted ones in many respects and deep planting is therefore recommended. In chickpea, none of the fungicide treatments improved the field performance of seeds. Dividend treatment rather reduced seedling root length. As in the case of bean, deepplanted seeds (10 cm) performed better than shallow planted ones (5 cm). In general, and in most respects, laboratory and field data correlated well. Moreover, recently released cultivars of all crops investigated, outperformed the older ones. This emphasises the need for replacing older cultivars with newer ones on a larger scale in Ethiopia. Large sized seeds are preferred to medium and the medium to small ones for all the crops investigated. Shallow planting for Ethiopian wheat cultivars, but deep planting for pulse cultivars, is recommended. Seed treatment with fungicides is imperative in wheat crops but is not as critical in pulse crops.

Hierdie studie is onderneem om inligting oor die kwaliteit van saad vir belangrike gewasse wat in Etiopië geproduseer word te verkry. Brood- en durumkoring stel die graangewasse voor terwyl akkerboon ("chickpea") en fababoon die peulgewasse verteenwoordig. Vir al die gewasse is twee cultivars ingesluit behalwe vir die durumkoring waar 'n derde Suid-Afrikaanse cultivar addisioneel bestudeer is. Alle proewe is by die Kleingraaninstituut, Bethlehem, Suid-Afrika uitgevoer onder laboratorium en veld toestande. Die hoofdoel van die studie was 1) om die saad van elke gewas in drie groottes te klassifiseer (klein, middelmatig en groot) en om die saad te karakteriseer in terme van korrelmassa, hektoliter-massa, persentasie vog en persentasie proteïen, 2) om die ontkiemingspotensiaal van onbehandelde- en swamdoderbehandelde saad onder laboratorium- en veldtoestande te bepaal, 3) om onder veldtoestande die potensiaal van verskeie saadlotte te bepaal, 4) om die invloed van twee saaidieptes op opkoms, opbrengs en ander opbrengs-parameters te ondersoek en 5) om statisties die cultivar, saadgrootte, saadbehandelingsmiddels en saaidiepte-interaksies te ondersoek. Van die twee Etiopiese broodkoring cultivars het Mitikie beter gevaar as Kubsa in die laboratorium sowel as onder veldtoestande vir meeste van die kwallteltspararneters wat geëvalueer is. Die hoofrede hiervoor blyk dat saad wat dieper geplant was, beter gevaar het omrede die saailinge langer koleoptiellengtes gehad het, en dit aan die anderkant positief geassosieer is met langer plante. As grondvog minimaal is, soos die geval is in die semi-ariede streke, is dit dus moontlik om saad van hierdie cultivar dieper as normaal te plant om die vog beter te kan benut. Oor die algemeen- het die kleiner broodkorinq-saac die slegste gevaar terwyl die groter saad die beste in terme van meeste van die parameters gevaar het. Die groot saadgrootte het 'n 13.8% opkoms van saailinge gehad en die plante het 'n 22.1% hoër opbrengs gelewer sowel as 'n 11.8% toename in die bogrondse bio-massa. Die invloed van swamdodersaadbehandelingsmiddels op die veldproef was minder duidelik as wat die invloed van saadgrootte was. Saailing-opkoms by 'n vlakker plantdiepte (5 cm) vir broodkoring was baie beter as by die dieper plantdiepte (9 cm) en die proteïeninhoud van die dieper plantdiepte was hoër as dié van die vlakker plantdiepte. Volgens die resultate verkry uit die proewe, het dit egter geblyk dat die vlakker plantdiepte vir die Oos-Vrystaat aanbeveel kan word. Durumkoring cultivars het baie soos die broodkoring gereageer. Saailinge van die semi-dwerg durumkoring cultivar, soos in die geval van die semi-dwerg broodkoring, het langer wortellengtes gehad as die lang-strooi cultivars. Ook het die semi-dwerg, Gerardo, oor die algemeen langer plante tot gevolg gehad as Orania en het die beste opbrengs vir die durums gelewer. Insekskade is opgemerk by saad van Kilinto en daarom kon die cultivar nie ten volle geëvalueer word nie. Groot durumsaad het beter gevaar as die medium en klein saad groepe in meeste aspekte. Swamdoder-behandelde saad het ook beter gevaar as onbehandelde kontrole saad. Saailingopkoms was beter by die vlakker plantdiepte, wat weerspieël is in beter opbrengste. Die geoeste sade se proteïeninhoud, soos in die geval van broodkoring, was betekenisvol hoër vir plante wat die dieper geplante sade voortgekom het, behalwe in die geval van Gerardo. Vitavax Plus behandelde saad wat diep geplant is, het opbrengste gelewer wat die betekenisvolste verhoging in die proteïeninhoud van durumkoring gehad het. As die twee fababoon cultivars vergelyk word, is dit duidelik dat Kuse beter gevaar het as Cs 20dk vir meeste van die parameters wat in die laboratorium- en veldproewe geëvalueer is. Soos die vorige twee gewasse, het die groot saad beter gevaar as die ander twee saadgroottes. Kleiner sade het saailinge met verrassend langer epikotiele gelewer, maar geen beduidende uitwerking is op die kwaliteit waargeneem nie. Saadbehandeling met Dividend het ook 'n verbeterde ontkieming van die fababoontjies teweegebring. Celest aan die ander kant, het die wortellengte van die saailinge verkort. Op grond van die uitslae van die ander gemete parameters, word Celest nie vir gebruik op fababoontjies aanbeveel nie. Die fababone wat diep geplant is, het beter gevaar in verskeie aspekte as met die vlakker plantdiepte, en daarom word die dieper plantdiepte aanbeveel. In die geval van akkerbone het nie een van die saadbehandelingsmiddels tot 'n verbetering onder veldtoedstande gelei nie. Dividend het inderwaarheid die saailingwortellengte verkort. Soos in die geval van die fababone het die dieper plantdiepte (10 cm) beter resultate gelewer as die vlakker plantdiepte (5 cm). Oor die algemeen het die laboratorium- en velddata goed gekorreleer. Ook het die nuwer vrygestelde cultivars beter as die ouer cultivars gevaar. Dit beklemtoon die feit dat ouer cultivars tot 'n groot mate vervang moet word met nuwe cultivars in Etiopië. Groter saadgroottes word verkies bo die klein saadgroottes in al die gewasse wat ondersoek is. Vlakker plantdieptes word aanbeveel vir Etiopiese koringcultivars, en dieper plantdieptes vir die peulgewasse. Saadbehandelingsmiddels met swamdoders is noodsaaklik vir koringgewasse maar is nie van kritiese belang vir die peulgewasse nie.
Dissertation (M.Sc.Agric. (Agronomy and Plant Breeding))--University of the Free State, 2000
Keywords: Wheat -- Yields; Chickpea -- Yields; Fava bean -- Yields